(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The purpose of the article is to reveal the peculiarities of the interaction of territorial communities and business in solving ecological problems on the ground. Accordingly the tasks of the work are finding out the content of territorial-private partnership; identification of financial and environmental risks in the activities of enterprises; substantiation of compromise ways of solving environmental problems originated by the activities of business structures in order to preserve jobs in individual territorial communities. On the basis of the study of foreign and Ukrainian economic literature has been elucidated that the important direction of building a socially-market economy to which Ukraine is heading is the financial stimulation of increasing socio-economic responsibility of business, territorial communities and households for the preservation of the environment. Proved that this development of such a component of the social economy as a territorial-private partnership can serve as the basis for this. The essence of the latter is in reconcilation of the economic interests of territorial communities and business in order to achieve the goals of sustainable development. One of the main goals of such development is the preservation of the environment and prevention of climatic warming. Revealed that the main financial and climatic risks in the activities of enterprises today are as follows: the increase of carbon tax rate; the need to shift from ussing of traditional types of energy to getting it with the help of restorative energy; reduction of so-called «dirty» investments that previously directed to the development of enterprises of traditional energy; strengthening the influence of territorial communities and environmental organizations on the adhere by enterprises to the environmental standarts of production. Substantiated that in order to stimulate the producers to realize the environmental measures at their enterprises in our country it is necessary more actively use at the local level such financial instruments of regulation of nature use as: the environmental tax incentives, «green» tariff, «green» loan, «green» foreign investments, and etc. Moreover the emphasis on the local level must be done not so much on penalties but on the financial incentives that encourage the business to introduce more modern environmental technologies.